Cocentaina, the people who rebelled against their lord for the scriptures of the condal Archive - Sánchez González, Antonio (Cuadernos de Historia Moderna, 2021)
The Count of Cocentaina held a series of festive events during the evening of November 2nd, 1751, with the sole purpose of distracting the people while he was secretly removing the Archivo Condal from the premises and taking it to Madrid. In those times, the nobility centralized their documental archives in Madrid in line with Borbonic centralism.This work aims to produce a detailed study of this archives’ contents, which contain a collection of legal documents concerning the Cocentaina county. It will also analyze the structure and organization of the archive and will also provide for a documentary description of the former.
Keywords: Cocentaina County; nobility archives; opposition to the lord; removal of archives; Borbonic centralism